Social Practices of The Warok In Bhuwuhan Tradition in Taropan Community - Nourma Ulva Kumala Devi; Darsono Wisadirana; Anif Fatma Chawa (Wacana Journal of Social and Humanity Studies, 2017)
Every celebration (hajatan) is related to the contribution custom or bhuwuh, especially the tradition in society of Taropan community in conducting routine Bhuwuhan. Bhuwuhan tradition is based on the Adep Asor value which is an attitude to honor the older relatives and the elder figures (Warok) during celebration. There is an agreement in Taropan community that is built by the Warok and the members to contribute and return the bhuwuhan during the celebration. This tradition is much conducted by the society in Pesawahan, Pedagangan and Tegalwatu villages. Therefore, the objectives of this research are to explain the routine bhuwuhan process that can be a tradition in Taropan community and analyze the social practices of Warok through the capital power-owned in order to preserve the bhuwuhan tradition in Taropan community. The research uses qualitative method by using case study approach through observation, interview and documentation. The research uses social practice theory of Pierre Bourdieu with structure analysis and agent through habitus discourse, arena and capital as the capacity of the actors. 1This custom is based on a strong kinship system and adep asor value between the members and the Warok by contributing and returning more bhuwuhan which are as a binder (investment) to make the kinship keep preserved. Moreover, social practices of the Warok to the members through the cultural, economic, social and symbolic capitals are determining the dominant position of the Warok in preserving the bhuwuhan tradition in Taropan community.